Hydrolysis of iodine labelled urodilatin and ANP by recombinant neutral endopeptidase EC. 3.4.24.11. - Abassi, Z A (1994)
1. Urodilatin is a 32 amino-acid peptide of similar sequence to atrial natriuretic peptide (ANP), with four additional amino-acids at the N-terminus. Although ANP and urodilatin bind to the same receptors with similar affinities, urodilatin is more active than ANP as a natriuretic agent. Previous studies, using neutral endopeptidase EC 3.4.24.11 (NEP) derived from crude membrane preparations, were inconclusive, but suggested that urodilatin was more resistant than ANP to degradation by this enzyme. In the present study, we compared the degradation rates of [125I]-urodilatin and [125I]-ANP by pure recombinant NEP (rNEP). 2. Incubation of radioactively labelled ANP with rNEP resulted in a much more rapid degradation of the peptide than that for labelled urodilatin. 3. Both phosphoramidon and SQ-28,603, potent inhibitors of NEP, completely protected both peptides from metabolism by rNEP. 4. The circular dichroism spectra of the two peptides indicate that they are very similar and exist largely in unordered or flexible conformations. 5. These results support the relative resistance of urodilatin to NEP, and indicate that urodilatin may be of use as a therapeutic agent, in conditions in which ANP is ineffective.